Commercialization and Business Feasibility of Campus Assets: Transforming Dormitories to Improve Financial Performance - Ahmad Nur Budi Utama; Agus Syarif; Bunga Ayu Wulandari (Bina Nusantara University, 2025)
The current era of globalization requires universities to formulate strategies to optimize campus assets to make them more productive and contribute to the institution. The research focused on one of the real assets at University of Jambi University, namely student dormitories. The research analyzed how to optimize dormitories to benefit students and the university. Problems faced by flat assets included limited land for maintenance, inadequate infrastructure, and high maintenance costs. Another challenge was the lack of supporting facilities, such as adequate reading rooms, laboratories, and sports venues. The research applied a mixed method (qualitative and quantitative approach). Qualitative analysis was carried out to evaluate business potential and identify opportunities for commercialization of dormitories through a survey of students living around campus. The data obtained was then analyzed using the Strengths, Weaknesses, Opportunities, Threats (SWOT) method to determine the strategic position of the dormitories. Meanwhile, quantitative data was obtained through observation and interviews, which were then analyzed using the investment criteria of Net Present Value (NPV) and Internal Rate of Return (IRR). The findings in SWOT show several suggestions for dormitory management at University of Jambi. Moreover, the results show that the NPV value of this 5-year flat project is estimated at IDR 571,256,867 with an IRR of 38.08%. It indicates that this project is feasible to implement. With the right strategy, the dormitories will not only be a place to live but also a place that supports students' academic and social growth.